Making the most of life: environmental choice during rearing enhances the ability of laying hens to take opportunities - Skånberg, Lena; Holt, Regine V.; Newberry, Ruth C.; Estevez, Inma; McCrea, Kirste; Keeling, Linda J. (Frontiers in Veterinary Science, 2024)
The potential of aviary housing for improving laying hen (Gallus gallus domesticus) welfare will be constrained if rearing conditions limit the hens' behavioral ability to take opportunities. Incorporating theories on developmental plasticity and animal agency, this study aimed to determine: (1) whether a choice of litter and perch types during rearing would promote long-lasting changes in use of novel locations and resources, and (2) the influence of timing of choice provision. Laying hen chicks were assigned to either a "Single-choice" (one litter and perch type) or "Multi-choice" environment (four litter and perch types) during "Early" (day 1-week 4) and "Late" rearing (week 5-15). The environments were switched in half of the 16 pens in week 5, resulting in a 2 x 2 factorial design with four choice environment by period combinations. The allocation of perch and litter space was the same across all treatment combinations. In week 16, all groups were moved to standard aviary laying pens (laying period, week 16-27). When first moved to the laying pens, hens with Multi-choice in either or both rearing periods were quicker to spread out in their pen than hens with Single-choice throughout rearing. Multi-choice in Early rearing also reduced the latency to use novel elevated structures (perches and nests) in the laying pens. Multi-choice during Late rearing increased success in finding and consuming hidden mealworms (tested in weeks 9-17) and increased the proportion of eggs laid on elevated nesting trays. Numerically, hens switched from Multi-choice to Single-choice in week 5 used the outdoor range less than hens switched from Single-choice to Multichoice. These results support the hypothesis that offering multiple resource choices during rearing improves hens' ability to make the most of new opportunities by being more proactive in exploring and exploiting newly available resources. In different opportunity challenges, hens showed positive outcomes in response to choice during Early, Late or both stages of rearing, suggesting that best results can be obtained by offering environmental choice throughout rearing.